The Implementation Of School-Based Management (MBS) At Arrohmah Islamic Elementary School Ambarawa District, Semarang Regency - Sari, Nila Ika; Ginting, Rosalina Br; Prayito, Muhammad (AJIS: Academic Journal of Islamic Studies, 2025)
This study aims to analyze the implementation of School-Based Management (MBS) at SDIT Ar Rohmah, Ambarawa District, Semarang Regency. SBM is an approach that grants greater authority to schools in managing various aspects of education, including teaching staff, curriculum, infrastructure, and school finances. This research adopts a qualitative approach with a phenomenological method involving interviews, observations, and documentation as data collection techniques. The main findings of this study indicate that SDIT Ar Rohmah has successfully implemented the principles of SBM, namely autonomy, participation, transparency, and accountability, although there are still some shortcomings. The school’s autonomy is reflected in the management of teaching staff and educational personnel, though the availability of academic staff, especially for cleaning and security tasks, remains insufficient. Stakeholder participation, including the school committee and parents, is well-executed in the planning and implementation of school programs. Transparency in financial management and reporting of learning outcomes has also been effectively applied. Accountability is evident in managing the School Operational Assistance (BOS) funds, which are conducted transparently and accountable. Recommendations include increasing the number of educational staff, forming a monitoring and evaluation team, diversifying funding sources, and improving the supervision of BOS fund utilization. This study contributes significantly to understanding how MBS can be effectively implemented in elementary schools in Indonesia and provides insights into the challenges faced during the implementation process.